The impact of climate change on the economic assessment of perennial green plants in the Chui region - Belek uulu Esenbek; Shakirova Klara; Nudel Sara; Melis uulu Danislan; Chortonbaeva Asel; Ishekeev Nazarkul (BIO Web of Conferences)
The article examines the impact of climate change on the economic assessment of perennial green spaces in the Chui region of the Kyrgyz Republic. The study includes analysis of data on climate change, crop yields and economic indicators over the past ten years. As a result of the study, main trends were identified, such as a decrease in the yield of perennial crops by 10-15%, an increase in operating costs by 20-25%, and a decrease in net profit by 15-20%. The need to introduce adaptation strategies, such as drip irrigation, selection of drought-resistant varieties and precision farming, which have reduced costs and increased yields, has been substantiated. In addition, the importance of government support, including subsidies for new technologies and adaptation programs, is emphasized, which contributes to the economic sustainability of agricultural enterprises. Long-term strategies aimed at developing new plant varieties and optimizing agricultural practices are seen as key measures to improve the resilience of the agricultural sector to climate change.